Optimasi Posisi Tawar Petani Kabupaten Jombang melalui Strategi Kemitraan Asosiasi Komoditas - Rohman, Fatkhur; Nareswari, Aptika Hana Prastiwi; Saptorini, Saptorini; Sutiknjo, Tutut Dwi; Rahardjo, Tjatur Prijo (JATIMAS : Jurnal Pertanian dan Pengabdian Masyarakat, 2024)
The partnership between farmers and commodity associations in food, horticulture, and plantation sectors holds significant potential to strengthen farmers' bargaining position in Jombang Regency. This initiative highlights various challenges farmers face in marketing their products, particularly regarding price negotiations and limited market access. By implementing partnership strategies through commodity associations, farmers are expected to optimize their bargaining position in both local and regional markets. The outreach method involved organizing meetings between farmers and commodity associations. These meetings aim to facilitate stakeholder dialogue to discuss marketing strategies, fair price setting, and strengthening distribution networks. Additionally, training is conducted to enhance farmers' capacity to negotiate and understand market dynamics. The results of this outreach activity indicated an improvement in farmers' understanding of marketing strategies and price negotiation. Moreover, farmers' access to local and regional markets has increased through networks built with commodity associations. This is reflected in farmers' increased incomes and the stability of agricultural products in Jombang Regency. The partnership between farmers and commodity associations (Comas) effectively enhances farmers' bargaining position. With strong collaboration between both parties, farmers can gain more significant benefits regarding fair prices and broader market access, thus improving farmers' welfare and food security in the Jombang Regency. Kemitraan antara petani dengan asosiasi komoditas pangan, hortikultura, dan perkebunan memiliki peluang besar untuk memperkuat posisi tawar petani di Kabupaten Jombang. Inisiatif ini menyoroti berbagai tantangan yang dihadapi petani dalam memasarkan produk mereka, terutama dalam hal negosiasi harga dan keterbatasan akses pasar. Dengan menerapkan strategi kemitraan melalui asosiasi komoditas, diharapkan petani dapat mengoptimalkan posisi tawar mereka di pasar lokal maupun regional. Metode pengabdian ini melibatkan penyelenggaraan pertemuan antara petani dan asosiasi komoditas. Pertemuan tersebut bertujuan untuk memfasilitasi dialog antara pihak terkait guna membahas strategi pemasaran, penetapan harga yang adil, serta penguatan jaringan distribusi. Selain itu, dilakukan pelatihan untuk memperkuat kapasitas petani dalam bernegosiasi dan memahami dinamika pasar. Hasil dari kegiatan pengabdian ini menunjukkan adanya peningkatan dalam pemahaman petani mengenai strategi pemasaran dan negosiasi harga. Selain itu, terdapat peningkatan akses petani ke pasar lokal dan regional melalui jaringan yang dibangun Bersama asosiasi komoditas (Askom). Hal ini tercermin dari peningkatan pendapatan petani dan stabilitas harga produk pertanian di Kabupaten Jombang. Adanya kemitraan antara petani dan Askom merupakan strategi efektif dalam meningkatkan posisi tawar petani. Kerjasama yang kuat antara kedua belah pihak, petani dapat memperoleh manfaat lebih besar dalam hal harga yang adil dan akses pasar yang lebih luas sehingga meningkatkan kesejahteraan petani dan ketahanan pangan di wilayah Kabupaten Jombang.